The Effect of Viral Marketing and Bandwagon Effect on Decision to Use Social Media Threads in Bekasi : Case Study on Social Media Threads Users in Bekasi - Carlos Tanuarto; Shenda Aprilia Christanti (Jurnal Indonesia Sosial Sains, 2024)
The purpose of this research was to analyze the effect of Viral Marketing, the Bandwagon Effect, on the Decision to Use Social Media Threads in the Bekasi Region. Data was collected by distributing questionnaires to 100 respondents who used Social Media Threads in the Bekasi area for at least 2 months. Sampling was carried out using non-probability sampling techniques and using purposive sampling. The analytical tool used is multiple linear regression; classical assumption tests (normality test, multicollinearity test, and heteroscedasticity test) are carried out as requirements that must be met in multiple linear regression analysis. Hypothesis testing simultaneously using the (F) test and partially using the (T) test. The results of this study indicate that viral marketing and bandwagon effect variables simultaneously affect customer satisfaction; this is evidenced by the F test with an Fhitung> Ftabel value (59.866> 3.09) and an amount of 0.552 (55.2%), viral marketing and bandwagon effect variables can be explained influenced by usage decisions while other variables outside this model influence the remaining 44.8%. While viral marketing partially / partially has an influence on usage decisions, this is proven by the T test with a value of Thitung> Ttabel of (5.423> 1.985) and has an influence of 0.231 (23.1%). And the bandwagon effect partially / partially has an influence on usage decisions; this is evidenced by the T-test with a Thitung> Ttable value of (9.859> 1.985) and has an influence of 0.498 (49.8%).